Microsurgical Clipping of Carotid-Ophthalmic Aneurysms. Case Series and Technical Details - Suárez, Mauro; Ardisana, Ernesto; Villalonga, Juan; Baldoncini, Matías; Campero, Álvaro (Revista Argentina de Neurocirugía, 2024)
Background. Carotid-ophthalmic aneurysms are the most common type of paraclinoid aneurysm; the emergence of new technologies has increased the popularity of endovascular therapy. However, endovascular treatment is associated with lower rates of complete occlusion. Furthermore, it cannot manage the mass effect on the visual pathway as efficiently as microsurgery. Objectives. To describe a series of carotid-ophthalmic aneurysms cases managed with microsurgical clipping and to report the results. Methods. Retrospective analytical study; a series of cases of patients with carotid-ophthalmic aneurysms undergoing microsurgical clipping is presented. The variables of age, gender, pre- and post-operative visual deficit, need for total, partial clinoidectomy or optic foraminotomy and the degree of aneurysmal exclusion in arteriography (complete or incomplete) were analyzed. Results. 15 patients were operated on, average age 55 years (40-67 years); 87% were female. Total clinoidectomy was performed in 7 cases, partial clinoidectomy in 4 and foraminotomy in 4 cases. Complete exclusion was obtained in 100% of cases. Furthermore, presurgical visual deficit improved or remained stable in 75% of cases and worsened in 25%. Conclusions. This case series demonstrates the effectiveness and safety of microsurgical clipping in carotid-ophthalmic aneurysms with aneurysmal occlusion rates of 100% and an improvement or stability of visual symptoms in the majority of patients, highlighting the validity of microsurgical clipping in the management of carotid-ophthalmic aneurysms.